Analysis Of Student Worksheet Needs In Science Practicum Activities With Problem-Based Learning Model - Siregar, Martina Eka; Masitoh, Siti; Sumarno, Alim (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
This study was conducted to analyze the needs of student worksheets in elementary school science practicum activities with a problem-based learning model. The needs analysis results will be the basis for making student worksheets. Needs analysis is carried out as an initial research stage on applying science practicum with a problem-based learning model. The study subjects were 10 grade IV students of SDN 010 Kundur. Researchers made observations and collected data through Google form questionnaires distributed via Whatsapp to students. Researchers also conducted interviews with class teachers related to the learning process. Researchers also conducted interviews with class teachers related to the learning process.